Indonesia : Report for the Post-Program Monitoring Discussions. (IMF Staff Country Reports; Country Report, 2005)
This paper presents Post-Program Monitoring Discussions for Indonesia. Macroeconomic and financial market developments were on the whole favorable in 2004. Inflation, after a temporary increase, peaking at 7u percent (y/y) in July, edged back down, ending the year at 6 1\2 percent. External developments were favorable. Besides a benign external environment, these favorable developments were helped by the overall sound economic policies pursued over the last few years. The IMF staff welcomes the government's commitment to improving the investment climate in the country.